Ca(2+) permeability of nicotinic acetylcholine receptors from rat dorsal root ganglion neurones - Fucile, Sergio (Blackwell Science Inc, 2005)
Ca(2+) entry through neuronal nicotinic ACh receptors (nAChRs) modulates many biological processes in nervous tissue. In order to study the functional role of nAChRs in peripheral sensory signalling, we measured their Ca(2+) permeability in rat dorsal root ganglion (DRG) neurones, and analysed the effects of nAChR-mediated Ca(2+) influx on the function of the vanilloid receptor TRPV1. The fractional Ca(2+) current (P(f), i.e. the percentage of current carried by Ca(2+) ions) flowing through nAChR channels was measured by Ca(2+) imaging fluorescence microscopy in combination with the patch-clamp technique. Functional nAChRs were expressed in a subset of adult DRG neurones (about 24% of the cells), typically with small to medium size as measured by their capacitance (40 ± 3 pF). In most cells, ACh evoked slowly desensitizing currents, insensitive to methyllycaconitine (MLA, 10 nm), a potent antagonist of homomeric nAChRs. Fast decaying currents, probably mediated by α7*-nAChRs (i.e. native α7-containing nAChRs), were observed in 15% of ACh-responsive cells, in which slowly decaying currents, mediated by heteromeric nAChRs, were simultaneously present. The nAChRs of adult DRG neurones exhibited a P(f) value of 2.2 ± 0.6% in the presence of MLA and 1.9 ± 0.6% (P > 0.1) in the absence of MLA, indicating that homomeric MLA-sensitive nAChRs do not contribute to Ca(2+) entry into adult DRG neurones. Conversely, 10% of neonatal DRG neurones showed ACh-evoked currents completely blocked by MLA. In these neurones, nAChRs showed a larger P(f) value (9.5 ± 1.5%), indicating the expression of bona fide α7*-nAChRs. Finally, we report that Ca(2+) influx through nAChRs in adult DRG neurones negatively modulated the TRPV1-mediated responses, representing a possible mechanism underlying the analgesic properties of nicotinic agonists on sensory neurones.